2023
DOI: 10.3892/etm.2023.11953
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 association with multidrug-resistant bacteria superinfections: Lessons for future challenges

Abstract: The future waves of COVID 19 infections will continue to raise serious problems in patients with severe forms of the disease. Bacterial infections associated with SARS-CoV-2 disease may complicate the progress of hospitalized patients with COVID-19. The present study aimed to evaluate the etiological spectrum of superinfection in adult patients with COVID-19 and to investigate the correlation between superinfection with multidrug-resistant (MDR) bacteria and serum procalcitonin (PCT). A total of 82 COVID-19 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…According to Susan et al, MDR bacteria were involved in 73.17% of COVID-19 patients with bacterial superinfections. Klebsiella pneumoniae, Enterococcus spp., and MRSA were the most common MDR bacteria identified in late infections after hospitalization in 20.43%, 4.30%, and 4.30% of all infections, respectively [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Susan et al, MDR bacteria were involved in 73.17% of COVID-19 patients with bacterial superinfections. Klebsiella pneumoniae, Enterococcus spp., and MRSA were the most common MDR bacteria identified in late infections after hospitalization in 20.43%, 4.30%, and 4.30% of all infections, respectively [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, in the present study, following an initial decrease, a second increase in CRP values was observed on days 10 and 15. A plausible explanation for this increase may be the onset of nosocomial infections, usually complicating the clinical course ( 38 , 39 ). Indeed, in patients critically ill with COVID-19, ICU-acquired bacteremia developed after a median time of 11 days after ICU admission, as shown in a previous study from the ICU ( 40 ).…”
Section: Discussionmentioning
confidence: 99%